Design And Manufacture Of Health Service Information Systems With The Scrum Method At The Web-Based Wm Clinic Bintaro - Alkautsar Setiawan, Nuranika Ramadhanti; Fauziyah, Fauziyah; Galih W, Raditya (Journal of Engineering, Technology and Computing (JETCom), 2024)
WM Clinic is an outpatient public clinic that provides primary health or health services including general poly, dental poly, physiotherapy, acupuncture, homecare, and payment. The current problem at WM Clinic is the frequent delays in handling health services due to the absence of service scheduling so that it cannot serve patients optimally, such as difficulty dividing patient service times that often clash. To deal with these problems, a web-based health service information system was designed and built using the scrum method as a system development method, PHP as a programming language and MySQL as a database, so that the health service process for patients becomes easier, faster and more accurate.